REAKSI PASAR MODAL INDONESIA TERHADAP COVID-19 SEBAGAI PANDEMI GLOBAL (Studi Empiris pada Perusahaan yang Terdaftar pada Indeks LQ45 tahun 2020) - Kamala, Novi Syaifatun; Fajar, Muhammad Andryzal (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2020)
This study aims to obtain empirical evidence of the absence of an average abnormal return, average volume trading activity, and bid-ask spread of stocks in the period around the event of the COVID-19 announcement as a global pandemic. The statement of the COVID-19 as the global pandemic of the World Health Organization (WHO) made the Indonesian capital market touch the lowest point at the level of 4,929.56. This study used the event study with the windows period for 11 days, which was five days before the announcement, the day of the announcement, and five days after the announcement. This type of research was a quantitative research using secondary data of the stock daily data obtained from the official website of the Indonesia Stock Exchange at www.idx.co.id and also some other sites that support such as Yahoo Finance. Sampling techniques used were purposive sampling and as many as 44 companies that meet data completeness criteria. The data analysis technique used was a non-parametric t-test using the Wilcoxon Signed-Rank test. The results of this study show that there is a difference in Average Abnormal Return in the period t-5 & t+5, t-4 & t+4, t-2 & t+2, and t-1 & t+1. The Average Trading Volume Activity indicates there is no significant difference in all periods of observation between before and after the announcement. Meanwhile, the Bid-Ask Spread shows a significant difference before and after the announcement in all periods for 11 days of observation.